TECHNOLOGY DEVELOPMENT OF NEW SUPPOSITORY ON THE BASIS OF GLYCYRRHIZA EXTRACT AND PARACETAMOL - G. M. Abdrakhmanova; S. K. Zhaugasheva; G. P. Pavelkovskaia (Фармация и фармакология (Пятигорск), 2015)
This work presents the study results of technologies of double-layer suppositories development of a new drug of combined effect using dense extract of Glycyrrhiza and paracetamol